Investment funds, risk-taking, and monetary policy in the euro area - Margherita Giuzio; Christoph Kaufmann; Ellen Ryan; Lorenzo Cappiello (European Central Bank (ECB), 2021)
We examine the transmission of monetary policy via the euro area investment fund sector using a BVAR framework. We find that expansionary shocks are associated with net inflows and that these are strongest for riskier fund types, reflecting search for yield among euro area investors. Search for yield behaviour by fund managers is also evident, as they shift away from low yielding cash assets following an expansionary shock. While higher risk-taking is an intended consequence of expansionary monetary policy, this dynamic may give rise to a build-up in liquidity risk over time, leaving the fund sector less resilient to large outflows in the face of a crisis.
Keywords: E32; G11; G23; 330; Monetary policy; non-bank financial intermediation; liquidity management; ECB